Comparison of central corneal thickness and intraocular pressure in gestational diabetic on diet control and normal pregnant women - Wei, Kan Kok (2017)
INTRODUCTION Pregnancy is known to cause increase in central corneal thickness (CCT) while reducing intraocular pressure (IOP) especially towards the end of gestation. However there is scarce published data on gestational diabetes on diet control. OBJECTIVE To compare the mean CCT and IOP between pregnant women with gestational diabetes (GDM) on diet control, healthy pregnant women and healthy non-pregnant women. METHODS This is a comparative cross sectional study. We recruited total of 184 women; 61 pregnant women with GDM on diet control, 63 healthy pregnant women and 60 healthy non-pregnant women as control. All pregnant women undergone once ocular examination during their 36-40 weeks of gestation. CCT measurement was done using specular microscope and IOP measured using non-contact tonometer. RESULTS There is statistically significant difference (p<0.05) in the mean CCT in women with GDM on diet control when compared to healthy pregnant and healthy non-pregnant women. No significant difference detected in the mean IOP among the groups. CONCLUSION GDM women have significantly thicker mean CCT compared to healthy pregnant and healthy non-pregnant women. The level of IOP was similar in all three groups.